Herpes Zoster Ophthalmicus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
A 17-month-old boy with HZO and delayed contralateral hemiparesis following intrauterine varicella exposure is reported from the Dept of Neurology, Univ Texas Med Sch, Houston, TX.